Improve Speaking Performance: A case Study of Using Youtube Videos Content Retelling - Nhung, Vuong Kim; Nguyen Thi, Xuan Hong (Technium Social Sciences Journal, 2025)
Improving English speaking skill has always been a major concern of both learners and educators. Therefore, it is necessary to explore specific ways to enhance this skill. While the employment of YouTube videos and storytelling has been found to bring certain advantages to enhancing learners’ speaking competence, this study focuses on exploring the effectiveness when combining these two techniques. Conducted over four weeks with 102 university students using action research approach and questionnaires for the study has found that YouTube Videos Content Retelling (YVCR) technique was effective in improving students’ speaking components, thereby supporting students with their speaking competence. Additionally, this method can also increase students’ motivation and engagement in speaking practice. Thus, findings from this research are useful for those who are seeking methods to enhance speaking competence as well as motivation for speaking practice.